Conserved exon 2 but a highly polymorphic 5'-UTR of Tyrosinase gene in Tianzhu White yak (Bos grunniens) - Zhang, H.; An, T.W.; He, J.W.; Luo, Y.Z.; Han Jianlin (Science Alert, 2012)
Domestic yak plays a critical role in supporting the livelihoods of nomads in the Central Asian Highlands. Tianzhu White yak is a unique breed developed from a very small number of mutant founders and its white hair has a special niche market value. In this study, the genetic polymorphisms in Tyrosinase (TYR) gene, which has been considered as a 'albino locus' in cattle, were identified and characterized to search for alleles associated with the white coat colour in yak. A total of 973 yak samples were collected, including 438 animals from five nucleus breeding herds and 365 individuals from four reproductive herds of the Tianzhu White yak. The reference TYR genomic DNA sequence derived from a Hereford bull was used to design all primers for screening and sequencing the exon 2 and the last partial 5'-untranslated region (5'-UTR) of the yak TYR gene. Both PCR-SSCP analysis and DNA sequences for their complete exon 2 in selected samples from the Tianzhu White yak herds and black yak populations identified a single conserved sequence identical to other cattle breeds. There were 14 genotypes and seven alleles defined by nucleotide polymorphisms present in the 215 bp long 5'-UTR of yak TYR gene among all yak samples, of which five alleles were specific to yak while the other two alleles were of a cattle origin. Although, current data suggested no association of these polymorphisms with the yak coat colour variations, they shed light on the potential function of the promoter on regulation of expression of yak TYR gene that is warranted to screen for additional polymorphisms in its extended 5'-UTR and other exons.